In House Training Module for Faculty & A Case Study - Dixit, G. M. N. (Journal of Engineering Education Transformations, 1994)
An attempt is being made to identify the training needs for the faculty to help institutional academic and administrative processes. The FACULTY constitutes personnel of the College who take part in imparting education.